The Meaning of Teaching for Early Childhood Teachers of Adult Male Teachers in Boyolali - Seno, S; Rosita, Kusnulia (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The purpose of this study was to determine the meaning of teaching for a male early childhood education educator. The life experiences of every male early childhood education educator are complex and unique, so the researcher chose this theme. In general, early childhood education educators in Indonesia are identical to the work of a woman, but some men still choose to work as early childhood education educators. Methodology: Data collection techniques using in-depth interviews (In-Depth Interviews). Data analysis used interpretive case study analysis. The subjects in this study were 3 people who were male early childhood education educators in Boyolali Regency. Results : The results of this study are the meaning of teaching for men who work as early childhood education educators is different. The main motivation for teaching early childhood education subjects is as a call to the soul to contribute to the intellectual development of the nation's children and as a charity. Subjects view welfare not only seen from the amount of salary received. Applications/Originality/Value: Positively perceived experiences in this study were self-actualization, being a life teacher, being a charity field, and commitment. Experiences that are perceived negatively in this study are the emergence of conflicts caused by a lack of confidence or conflicts that come from external.